The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/pits.22533
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating the indigenous evaluation framework for culturally responsive community engagement

Abstract: Native American families, schools, and communities foster resilience among their youth who experience significant mental health disparities. To increase equity in mental health services for Native American students, it is essential that researchers employ culturally responsive community engagement when developing programs in schools. Guided by the Indigenous Evaluation Framework and Tribal Critical Race Theory, the aim of the current study was to examine our process of community engagement in the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In addition, we found that papers in this review generally discussed the identified risk and protective factors as being universally applicable, with the exception of gender differences in a few articles. Yet, best practice in prevention and intervention design suggests that culturally and contextually appropriate programming is required to meet youths’ needs and to advance equity-centered and socially just prevention ( 2 , 67 , 68 ). Despite this, there was little noted in the included articles about particular risk and protective factors specific to any racial or cultural groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that papers in this review generally discussed the identified risk and protective factors as being universally applicable, with the exception of gender differences in a few articles. Yet, best practice in prevention and intervention design suggests that culturally and contextually appropriate programming is required to meet youths’ needs and to advance equity-centered and socially just prevention ( 2 , 67 , 68 ). Despite this, there was little noted in the included articles about particular risk and protective factors specific to any racial or cultural groups.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CAE is a relational process and perspective that aims to inform ourselves, as researchers, of the social phenomenon we study (Hernandez et al, 2017). To our knowledge, there is only one study in school psychology that has been conducted using CAE (See Goforth et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Evaluations can also engage communities without using formal participatory methods such as CBPR. Similarly, Goforth et al (2021 ) undertook a process evaluation of a public-school community engagement initiative with Confederated Salish and Kootenai Tribes in the United States to increase mental health program service access. Context, relationships, equity of partnership, culturally relevant methodologies (e.g., storytelling), tribal and community empowerment and leadership, and meaningful "immersion in the community, including learning about the historical and cultural context" (p. 2) were key features in their approach.…”
Section: Insights: Evaluation Principles Approaches and Methodsmentioning
confidence: 99%